E-commerce platform & its opportunities in Bangladesh: A study on Kablewala Bangladesh Corporation. - Babli, Jannatul Naima (Brac University, 2021)
This internship report is submitted in partial fulfillment of the requirements for the degree of Masters of Business Administration, 2021.